Genera Jamur Patogen dan Persentase Penyakit Bercak Daun yang ditemukan pada Pertanaman Sawi Hijau (Brassica juncea) di Desa Serang, Kecamatan Karangreja, Purbalingga - Nia Sri Hartatik; Eddy Tri Sucianto; Endang Sri Purwati (BioEksakta : Jurnal Ilmiah Biologi Unsoed, 2020)
Green mustard (Brassica juncea) is an annual or horticultural plant of the Brassica genus. The purpose of this research is to knowledge the type of fungi that cause leaf spot disease on green mustard plants and to know the large percentage of leaf spot diseases caused by fungus on mustard greens in Serang Village, Karangreja District, Purbalingga. This research is used survey method by taking purposive random sampling at two different locations. The type of fungus that causes leaf spot disease on (B. juncea) mustard green can be identified by isolating the part of plants are sick then identified. Identification of fungi is doing by two stages of observation, that is observation macromorphological characters and micromorphological characters. Observation of macromorphological characters includes colony color, colony shape, the edge of colony shape and colony reverse color. Observation of the micromorphology character includes the presence of hyphae, hyphae (insulated or non-insulated), conidia shape, conidia color, additional devices and conidiophores. The next stage to find out the type of fungus that causes leaf spot disease is Koch's Postulate.The results obtained there is one type of disease in green mustard plants. Leaf spot is one of the diseases of mustard greens caused by the fungus Alternaria sp, with a frequency of leaf spot disease as many as 196 times, and the percentage of disease of 51,30%.